Firearm Ownership and Suicide Rates Among US Men and Women, 1981–2013 - Siegel, Michael; Rothman, Emily F. (American journal of public health (1971), 2016)
Objectives. To examine the relationship between state-level firearm ownership rates and gender-specific, age-adjusted firearm and total suicide rates across all 50 US states from 1981 to 2013. Methods. We used panel data for all 50 states that included annual overall and gender-specific suicide and firearm suicide rates and a proxy for state-level household firearm ownership. We analyzed data by using linear regression and generalized estimating equations to account for clustering. Results. State-level firearm ownership was associated with an increase in both male and female firearm-related suicide rates and with a decrease in nonfirearm-related suicide rates. Higher gun ownership was associated with higher suicide rates by any means among male, but not among female, persons. Conclusions. We found a strong relationship between state-level firearm ownership and firearm suicide rates among both genders, and a relationship between firearm ownership and suicides by any means among male, but not female, individuals. Policy implications. For male persons, policies that reduce firearm ownership will likely reduce suicides by all means and by firearms. For female persons, such policies will likely reduce suicides by firearms.